Fibrillary glomerulonephritis or complement 3 glomerulopathy: a rare case of diffuse necrotising crescentic glomerulonephritis with C3-dominant glomerular deposition and positive DNAJB9. Issue 2 (18th February 2021) - Baker, Lyle Wesley; Khan, Mahnoor; Cortese, Cherise; Aslam, Nabeel
Abstract : Fibrillary glomerulonephritis (FGN) and complement 3 glomerulopathy (C3G) are rare forms of glomerulonephritis with distinct aetiologies. Both FGN and C3G can present with nephritic syndrome. FGN is associated with autoimmune disease, dysproteinaemia, malignancy and hepatitis C infection. C3G is caused by the unregulated activation of the alternative complement pathway. We present a rare case of diffuse necrotising crescentic glomerulonephritis with dominant C3 glomerular staining on immunofluorescence—consistent with C3G—but electron microscopy (EM) findings of randomly oriented fibrils with a mean diameter of 14 nm and positive immunohistochemistry for DNAJB9—suggestive of FGN. To the best of our knowledge, this is the first reported case of FGN to show dominant C3 glomerular deposits. This case report reaffirms the utility of EM in the evaluation of nephritic syndrome and highlights the value of DNAJB9—a novel biomarker with a sensitivity and specificity near 100% for FGN.